2019
DOI: 10.3390/agronomy9100656
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Evaluation of Essential Oils from Mediterranean Aromatic Plants against the Mushroom Cobweb Disease, Cladobotryum mycophilum

Abstract: The main aim of this study was to evaluate the use of essential oils (EOs) as an alternative to synthetic fungicides used in the control of cobweb disease of button mushroom (Agaricus bisporus) caused by Cladobotryum mycophilum. The EOs used were obtained by hydrodistillation from five Mediterranean aromatic species (Lavandula × intermedia, Salvia lavandulifolia, Satureja montana, Thymus mastichina, and Thymus vulgaris), analyzed by gas chromatography, and tested in vitro for their antifungal activity against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The disease is prevalent especially in A. bisporus. Gea et al [24] and Kim et al [25]. The prevention and control of the disease is mainly based on the principle of "Prevention rst, comprehensive prevention and control", strictly control the production of each link, prevent the invasion of pathogens, if the disease after the application of chemical pesticides for prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is prevalent especially in A. bisporus. Gea et al [24] and Kim et al [25]. The prevention and control of the disease is mainly based on the principle of "Prevention rst, comprehensive prevention and control", strictly control the production of each link, prevent the invasion of pathogens, if the disease after the application of chemical pesticides for prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo bioassays conducted by Gea et al [52] showed that essential oils obtained from Thymus vulgaris and Satureja montana, were the most effective for inhibiting the mycelial growth of Cladobotryum mycophilum, and were also the most selective to A. bisporus. According to the authors, these essential oils may be useful products to manage the mushroom cobweb disease if used as a part of an integrated pest management (IPM) program.…”
Section: Discussionmentioning
confidence: 99%
“…EOs from cinnamon, geranium, and spearmint completely inhibited the growth of C. dendroides , both by contact and the volatile phase were efficient, but low selectivity was reported, and the authors suggested the EOs can damage the host mycelium [ 76 ]. EOs from the Mediterranean aromatic plants Thymus vulgaris (main compounds p-cymene and thymol) and Satureja montana (main compounds carvacrol and p-cymene) were selective and efficient to inhibit mycelial growth of C. mycophilum in vitro , and reported significant control of cobweb disease, comparable to the fungicide treatment with metrafenone, when infected A. bisporus crops were treated with these EOs at 1%; although crop losses were noted in the first flush, suggesting some fungitoxic effect and crop delay [ 61 ]. The impact of cobweb disease in Agaricus and Pleurotus crops was also reduced significantly by the active component of the biofungicide Timorex 66 EC, tea tree oil; however, it showed significantly lower toxicity against C. dendroides mycelium than prochloraz-Mn in vitro [ 58 , 96 ].…”
Section: Cobweb Disease ( Cladobotryum Spp)mentioning
confidence: 99%